PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN MATEMATIKA KELAS V SD INPRES PACCINONGANG - Rahmat Hidayat; Nur Laely (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to improve learning outcomes in the Mathematics subject for fifth grade students at SD Inpres Pacciongang by using the Problem Based Learning learning model. By implementing the Problem Based Learning learning model, it will improve student learning outcomes because implementing the PBL model with concrete media can be an effort to improve mathematics learning outcomes. The subjects of this research were class V students at SD Inpres Pacciongang consisting of 25 students, 10 male students and 15 female students. This type of research uses Classroom Action Research (PTK). Each cycle has stages, namely planning, implementation, observation and evaluation, and reflection. The results of this research show that the average score after implementing the Problem Based Learning learning model has increased, namely from 71% to 83%. Likewise, students' learning completeness has increased from cycle I and cycle II. According to the observation results, there was an increase from cycle I and cycle II. The ability to analyze also increases significantly. This is because students are used to it.